Massive Hematochezia from a Large Bleeding Duodenal Diverticulum. (9th June 2021) - Esteban, Marcus Juan; Sureen, Amit; Herlihy, Daniel; Elhanafi, Sherif; Zuckerman, Marc J.
Abstract : Background . Duodenal diverticula are a rare cause of gastrointestinal (GI) bleeding despite being a common finding in the GI tract. We present a case of a patient who had massive hematochezia due to a complex duodenal diverticulum. Case Presentation. A 74-year-old Hispanic female presented initially with generalized weakness. During admission, the patient had an episode of a large amount of hematochezia and had to be transferred to the intensive care unit (ICU). Upper endoscopy was done using a forward-viewing endoscope which revealed a bleeding complex duodenal diverticulum. Successful hemostasis was achieved through epinephrine injection followed by placement of hemostatic clips. Conclusion . Although rare, gastroenterologists need to be aware of duodenal diverticulum as a possible cause of gastrointestinal bleed. It could be life-threatening, and thus, prompt diagnosis and management is necessary.